أساليب إغواء الشيطان لبني آدم : دراسة نموذجية في ضوء القصص القرآني - مأكينج، فرقان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research aims at carrying out a typical study in the light of Quranic stories on “The methods of Shayṭᾱn (Satan) in seducing mankind”. Thus, Allah the Almighty has informed us in the Holy Qur'an that the misguidance only occurred to the previous nations from Satan. Likewise, Satan remains to misguide the children of Adam till the last day; So, no one can escape from his trick and temptation except by identifying the real identity of Satan and his evils, as well as the fact that his aggression is against mankind. This can be discovered by adopting an inductive method to derive the methods of Satan in seducing the children of Adam, through the stories mentioned in the Qur'an, and by mentioning the effects of Satan tricks on the sons of Adam. Therefore, the researcher has followed two methodologies in this research: first an inductive approach gathering most of the addition's verses of the Qur'an and texts related to the tricks and temptations of Satan, and the story of his seduction that mentioned in the Qur'an will be studied. Likewise, other related kinds of literature, magazines and websites will be reviewed. More so, an analytical approach has been applied in the research to analyse the verses of the Qur'an, exegetic opinions of the scholars, and to derive the proof from the related sources to reveal the objective of the Qur'an on the topics related to the seduction of Satan to mankind. The researcher has reached some important conclusions, among which the main one is the fact that Satan has various methods of seduction to achieve his goal, which was the permission that he sought from Allah to be able to mislead mankind. Thus, Satan misled many people among the previous generations; many of them went astray, while many others failed to acknowledged Allah's favour upon them.